The Development of Uninterruptible Power Supply For Personal Computers - Jarushi, Ali Milad (2000)
Computer systems have become very important all over the world. They are capable of doing complicated works. When the main power falls, the computer system cannot support. Its normal operation and it will shut down immediately. Consequently, all working data will be lost if they are not saved previously. Therefore, an uninterruptible power supply (UPS) should be designed to protect data loss and to prevent any output interruption during a power failure. The objective of this project is to design, construct, and test UPS for personal computers. The proposed UPS is cheaper and its size is smaller than that of the conventional UPS available in the market. The proposed UPS consists of rectifiers, a battery charger, an automatic controller, a sealed lead acid battery, regulators and a boost DC-to-DC converter. The proposed UPS is capable of supporting the normal operation of the PC for 20 minutes during power failure. This 20-minute time is enough for the user to save the current work on the PC and switch off the PC properly. The detailed analysis of the design, experimental works and simulation are discussed in this report. Results of the experimental and simulation work showed that there was a good agreement between the hardware and software. This indicated that UPS was successfully developed.